Integration of Entrepreneurial Values into Economic Education Learning in Primary Schools - Azan; Eli, Wa Ode; Bandje, Yanto (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2025)
Instilling entrepreneurial values from an early age is a strategic step in shaping students' character and life skills. Economic education at the elementary school level holds great potential as a platform to integrate these values into the learning process. This study aims to examine the effect of integrating entrepreneurial values into teaching on students’ learning outcomes. The research employed a quantitative method with a quasi-experimental design using a pretest-posttest control group model. The subjects consisted of two groups: an experimental class that received instruction integrated with entrepreneurial values, and a control class that received conventional teaching. Data were collected through learning outcome tests administered before and after the intervention. The analysis results showed a significant difference in student learning outcomes between the two groups. The experimental group demonstrated greater improvement in learning outcomes compared to the control group. A t-test revealed a statistically significant difference, and the effect size calculated using Cohen’s d indicated a strong impact of the treatment. In conclusion, the integration of entrepreneurial values into the learning process proved to be effective in enhancing students’ academic performance and contributed to the development of entrepreneurial character. This approach may serve as an innovative alternative in elementary education curriculum development.